2015
DOI: 10.1186/s13071-015-0815-4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of Texas hunters: a potentially high-risk population for exposure to the parasite that causes Chagas disease

Abstract: BackgroundChagas disease is a parasitic infection transmitted to humans and mammals by the Triatominae insect. If untreated, Chagas disease can lead to heart failure and death. Previous publications highlighted the potential public health risk of disease transmission among hunters in the United States.FindingsWe further investigated this population’s risk by administering a knowledge, attitudes, and practices questionnaire. Responses from hunters detailed the vector exposure and hunting practices unique to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Within the state, sylvatic transmission cycles have been reported with seven different vector species and 27 sylvatic mammalian reservoirs [10]. The potential for sylvatic spillover to humans in this region has been implicated from increased outdoor exposure and interactions in rural environments [13]. In addition, colonias (primarily Hispanic communities) in this region of Texas have unprecedented poverty rates and living conditions that allow for easy access for vectors to enter and colonize homes, which might place residents at an increased risk of domestic transmission [5, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Within the state, sylvatic transmission cycles have been reported with seven different vector species and 27 sylvatic mammalian reservoirs [10]. The potential for sylvatic spillover to humans in this region has been implicated from increased outdoor exposure and interactions in rural environments [13]. In addition, colonias (primarily Hispanic communities) in this region of Texas have unprecedented poverty rates and living conditions that allow for easy access for vectors to enter and colonize homes, which might place residents at an increased risk of domestic transmission [5, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Activities that require frequent contact with domestic and wild animals could elevate the risk for human infections. Hunters have been recognized as a potential high‐risk group due to the extended amount of time they spend outdoors and the risk for blood‐borne exposure during the field dressing process (Yaeger, ; Barr et al., ; Pung et al., ; Bern et al., ; Cantey et al., ; Garcia et al., , ). A survey conducted with a wildlife management association in south central Texas found that the vast majority of hunters (93%) reported field dressing their game animals.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been well documented that triatomine bugs are endemic in Texas with over half typically found to be T. cruzi positive (Kjos et al, 2009;Curtis-Robles et al, 2015;Wozniak et al, 2015), the appropriate studies designed to fully understand the burden of disease among the Texas wildlife, domestic animal and human populations have not yet been Packchanian, 1942;Burkholder et al, 1980 Opossum (Didelphis virginiana) 71/399 18 Packchanian, 1942;Eads et al, 1963 Raccoon (Procyon lotor) 24/54 44 Schaffer et al, 1978;Burkholder et al, 1980;Charles et al, 2013 Packchanian, 1942;Eads and Hightower, 1952;Pippin, 1970;Burkholder et al, 1980;Ikenga and Richerson, 1984;Pinto et al, 2010;Charles et al, 2013 Burkholder et al, 1980;Ikenga and Richerson, 1984;Meurs et al, 1998;Beard et al, 2003;Shadomy et al, 2004;McPhatter et al, 2012;Tenney et al, 2014 Activities that require frequent contact with domestic and wild animals could elevate the risk for human infections. Hunters have been recognized as a potential high-risk group due to the extended amount of time they spend outdoors and the risk for blood-borne exposure during the field dressing process (Yaeger, 1961;Barr et al, 1991;Pung et al, 1995;Bern et al, 2011;Cantey et al, 2012;Garcia et al, 2014aGarcia et al, , 2015. A survey conducted with a wildlife management association in south central Texas found that the vast majority of hunters (93%) reported field dressing their game animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this were indeed where he was infected, then this case would represent the first autochthonous case in Arizona. The patient had history of residence in Texas, another known area of local transmission (Garcia, Murphy, Gross, Wagner, & Murray, ); however, he had only been living in Texas for a year prior to first testing positive and did not report seeing any triatomines at this residence. While less likely, we cannot rule out the potential of vector exposure during the frequent military exercises in states with known sylvatic transmission.…”
Section: Case‐patient Reportmentioning
confidence: 99%